PERKEMBANGAN FITRAH BERAGAMA ANAK DAN IMPLIKASI PEMBINAANNYA: TINJAUAN PSIKOLOGIS (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2002)
Children's fitrah to hace a religion develops in three phases; myth, fact, and individual. It's charateristics, among others, are; less profound, egocentric, anthropomorphic, verbal, ritual, imitative and amazement. Efforts to build children's fitrah to have religion can be done by giving adequate religious education and experiences, making the children accustomed to religious practices, and being good models for children.